Peran Pustakawan Sebagai Mitra Pendamping Penulisan Karya Tulis Ilmiah Mahasiswa Universitas Muhammadiyah Magelang - Atin Istiarni (Media Pustakawan, 2021)
The academic librarians have now penetrated into academic activities, namely becoming research partners of the academic community. The librarian's job is no longer just to borrow and return books. However, librarians can also provide mentoring services for the preparation of scientific papers based on partnerships with students and lecturers. The purpose of this study is to (1) inform the existence of academic writing guidance service. with librarians at the University of Muhammadiyah Magelang, (2) find out the urgency of academic writing guidance service. in libraries, (3) the mechanism of library academic writing guidance service., and (4) the informant's response to the academic writing guidance service.. The type of data in this study is descriptive qualitative with data sources from interviews, questionnaires, and document studies. Research informants were 7 people consisting of 1 lecturer and 6 students. The results showed that; (1) Academic writing guidance service. with librarians are very helpful for lecturers and students in preparing theses, (2) librarians are very clear, detailed, and responsive in providing guidance, and (3) Academic writing guidance service. are very important and needed for students to Academic Writing becomes structured and systematic. Suggestions given by informants for academic writing guidance service. to improve service promotion and form mentoring WhatsApp groups.